El modelo de negocio de Airbnb: Un enfoque innovador en la industria hotelera - José Morelos Gómez; Edith Romero Martínez (Mundo Fesc)
This research analyzes the impact of Airbnb on the hotel industry and how it has changed hotel companies ' approach to customers. Three main aspects are explored: Airbnb's impact on the industry, hotel companies' adaptation to disruptive innovation, and the factors that influence success and sustainability in the new competitive environment. The methodology used was a bibliographic review of the most relevant scientific articles, in which 638 articles were filtered ; a second selection phase resulted in a reduction to 20 final documents. The results identify emerging trends and practices in the hotel industry, confirming that Airbnb has generated significant changes in the demand and supply of accommodation, the pricing and rate structure, and the competitive and collaborative relationships between Airbnb and traditional hotels. In addition, the study examines the strategies adopted by hotel companies to adapt to this new environment, including the differentiation and personalization of the customer experience, the implementation of technologies and business models based on the sharing economy, and the redefinition of organizational structure and talent management. Finally, key factors for success and sustainability in this new context are identified , such as service quality and customer satisfaction, product and service innovation, and social and environmental responsibility in the hotel industry.